Temperature dependent charge conduction and relaxation mechanism study of nano-structure WO3 by impedance spectroscopy. (20th December 2019) - Khan, Ayaz Arif; Khan, Muhammad Nasir; Iqbal, Mazhar; Majeed, Asif; Jalil, Abdul; Mukhtar, Surayya; Javed, Muhammad
Abstract: Impedance spectroscopy is employed to probe the dielectric and electric transport mechanism in hierarchical flower like WO3 micro-structure. The electro-active regions defined from the impedance spectroscopy in the frequency range up 40Hz -110MHz explained by the existence of grains (bulk) and grain boundary phases in this hierarchical WO3 micro-structure. Modulation of impedance plane plots has been thrashed out due to the variation of relaxation-time with temperatures. An equivalent circuit model (Rgb Qgb ) (Rg Qg ) is employed to explain impedance plane plots. Overlapped large-polaron tunneling and correlated-barrier hopping transport mechanism is observed in the investigated temperature range. The detailed study of the electrical transport properties of WO3 shows that the impedance and allied parameters are strongly depending on temperature and its microstructure as well. The lower value of dielectric loss at 1MHz makes WO3, a potential material for high frequency application.